Effigy of a templar, Robert Ros - Allen, T. (Tufts Archival Research Center, 2005)
Figure also identified the second lord Ros. This illustration is from the History and Antiquities of London, Westminster, Southwark and parts adjacent, vol. 4, by Thomas Allen.